Nonsense Suppression of the Major Rhodopsin Gene of Drosophila - Washburn, T. (1992)
We placed UAA, UAG and UGA nonsense mutations at two leucine codons, Leu(205) and Leu(309), in Drosophila's major rhodopsin gene, ninaE, by site-directed mutagenesis, and then created the corresponding mutants by P element-mediated transformation of a ninaE deficiency strain. In the absence of a genetic suppressor, flies harboring any of the nonsense mutations at the 309 site, but not the 205 site, show increased rhodopsin activity. Additionally, all flies with nonsense mutations at either site have better rhabdomere structure than does the ninaE deficiency strain. Construction and analysis of a 3'-deletion mutant of ninaE indicates that translational readthrough accounts for the extra photoreceptor activity of the ninaE(309) alleles and that truncated opsins are responsible for the improved rhabdomere structure. The presence of leucine-inserting tRNA nonsense suppressors DtL(a) Su(+) and DtL(b) Su(+) in the mutant strains produced a small increase (less than 0.04%) in functional rhodopsin. The opal (UGA) suppressor derived from the DtL(a) tRNA gene is more efficient than the amber (UAG) or opal suppressor derived from the DtL(b) gene, and both DtL(a) and DtL(b) derived suppressors are more efficient at site 205 than 309.